Assessment of nutritional quality of selected rural youth and the nutrition related practices of their families - Shiny R L (Department of Home Science, College of Agriculture, 2004)
The study entitled “Assessment of nutritional cognition of selected rural youth and nutrition related practices of their families” was undertaken. The locale of the study was Neyyattinkara taluk of Thiruvananthapuram district. The objective of the study was to assess and compare the nutrition knowledge and nutrition attitude of rural youth belonging to farm and non-farm families. The nutrition related practices of the families were also assessed. Equal number of the respondents from farm and non-farm families were drawn for the study comprised of 160 rural youth (80 male and 80 female) from two wards of the selected two panchayats. The dependent variables selected included nutrition knowledge and nutrition attitude. The independent variables included socio-economic variables like caste, religion, family size, family type, family income, land size, household food production and type of house. A comprehensive analysis of socio-economic and personal characteristics along with nutrition knowledge and attitude of the selected rural youth were carried out using appropriate tools and methods. The socio-personal characteristics revealed that majority belonged to 18-20 years. Majority had education upto pre-degree level and belonged to first born category. Fifty per cent of the respondents, both from farm and non-farm families had no income of their own. The respondents got major source of information from television. Their social participation revealed that many of them were members of various organizations. The socio-economic status of the families found that majority belonged to Hindu forward caste hailed from nuclear families having monthly income between Rs. 5001-10,000. Non-farm families did not cultivate any crops in their possessed land. In the case of farm family at least one acre of land was possessed by each were cultivated major and minor crops. Their farm produce like paddy, vegetables and fruits were fully utilized by them. While analysing their overall nutrition knowledge scores it was found that majority of the respondents had medium level knowledge and the farm families possessed better knowledge than non-farm families. When the nutrition awareness of the respondents in selected areas of nutrition was studied it was found that many of the respondents had better knowledge in cooking methods without nutrient loss while only a small percentage had correct knowledge on nutrition deficiency disorders. The attitude level of the respondents was measured using specially designed attitude scale. It was revealed that majority possessed higher score in neutral level i.e., they had neither favourable nor unfavourable attitude. It was found that in the areas of importance of good nutrition, food habits and nutrition education higher per cent of the respondents showed neither favourable nor unfavourable attitude. Among the rural youth the females have a higher nutritional cognition when compared to their male counterparts. It is noted that the selected independent variable, age had a negative relationship with knowledge whereas other independent variables like caste, marital status and birth order had no relationship with knowledge and attitude of the respondents. Dietary habits of the respondents revealed that majority were non-vegetarians. Regarding nutrition related practices it was found that majority were good eaters and had possessed nibbling habits. Most of the respondents especially females skip one meal a day particularly breakfast. In the case of frequency of use of different foods it was found that rural youth consumed pulses, green leafy vegetables and meat in lesser quantity. While rating nutrition related practices of the families it was found that majority followed the practices in a moderate level and there is not much difference between farm and non-farm families. The interrelationship with nutrition knowledge and nutrition attitude and practice revealed that there exists a significant positive relationship between nutrition knowledge and attitude but not with practice. Information source utilization of the youth had a positive relationship with nutrition knowledge and nutrition attitude whereas it showed no relationship with the practices followed in their families. Overall assessment of nutrition cognition of rural youth was found to be unsatisfactory and clarity in the concepts of applied nutrition was lacking among the respondents studied. The results of the study emphasized the need for nutrition intervention programme specially targeted to rural youth.